2004
DOI: 10.1007/s00267-004-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Land-Cover and Mangrove Structures with Remote Sensing Techniques: A Contribution to a Synoptic GIS in Support of Coastal Management in North Brazil

Abstract: This article deals with the development and application of a cartographic database for a synoptic Geographic Information System (GIS). Its purpose is the storage and evaluation of the heterogeneous datasets of the interdisciplinary scientific research program MADAM (Mangrove Dynamics and Management), which aims to develop recommendations for a tailored integrated coastal management scheme for the mangrove ecosystem at Braganca (North Brazil). The article describes the integration of remote sensing data, aerial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 25 publications
0
40
0
2
Order By: Relevance
“…The results showed that the developed rule set was able to map targeted mangrove composition objects from images with different spatial resolutions. Only limited studies have implemented the explicit hierarchical model of objects in mangrove mapping [9,12,16,69]. This study demonstrated the effectiveness of having a conceptual hierarchical model for mangrove mapping.…”
Section: Mangrove Composition Mapsmentioning
confidence: 87%
“…The results showed that the developed rule set was able to map targeted mangrove composition objects from images with different spatial resolutions. Only limited studies have implemented the explicit hierarchical model of objects in mangrove mapping [9,12,16,69]. This study demonstrated the effectiveness of having a conceptual hierarchical model for mangrove mapping.…”
Section: Mangrove Composition Mapsmentioning
confidence: 87%
“…These included peer-reviewed journal articles, conference papers and chapters of book and PhD thesis publications. This review specifically focused on vegetated wetlands (i.e., colonized by aquatic macrophytes) of diverse types [36] such as fresh-and salt-water estuarine, riverine, lacustrine, palustrine and selected marine (mangrove) ecosystems (Table 1, [5][6][7][8]12,13,[15][16][17][18][22][23][24][25][26][27][28][29][30]32,34,) and excluded studies of solely deepwater and open-water aquatic ecosystems such as seagrass beds. The OBIA applications and main research objectives fell into several broad groups (with some papers applicable to more than one of these):…”
Section: Research Objectives and Focusmentioning
confidence: 99%
“…In OBIA, the images are first segmented into "objects" that are groups of pixels representing ground patches, entities or their elements (primitives) which subsequently can be classified into categories of interest by unsupervised, supervised or rule-based algorithms [14,19,20]. The key benefits of OBIA relative to pixel-based methods include: (1) the possibility to incorporate object-level shape, texture and relevant contextual variables into classification, in addition to spectral values of the input image layers [19,20]; (2) smoothing some of the local variation within objects, which may reduce the salt-and-pepper noise and enhance classification accuracy [13,17,21,22]; and (3) accounting for the landscape hierarchy of patch, cover type and ecosystem structure by working with multiple object layers nested within each other at different spatial scales [23][24][25][26]. The approximation of ground entities and patches by image objects makes them more ecologically relevant and potentially more resilient to minor geospatial positioning and image registration error than pixel units [5,27].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing imagery has been used to map coastal topography and flooding [56,63,[82][83][84][85][86] and to map physiological responses of vegetation to salinity or pollution [87][88][89][90]. Some studies have used remote sensing to map coastal or vegetation change over time at two, or a few, time points [91][92][93][94][95][96][97], including analyses of effects of invasive species [59,98]. However, mapping vegetation or topography at even a few points in time provides insufficient evidence to validate the theoretical dynamic equilibria, oscillations, or rapid state changes that would characterize systems truly exhibiting multiple stable states.…”
Section: Invoking Multiple Stable State Theorymentioning
confidence: 99%